Can mean platelet volume be used as a biomarker for asthma? - Nacaroglu, Hikmet Tekin; Isguder, Rana; Bahceci, Semiha Erdem; Ceylan, Gökhan; Korkmaz, Huseyin Anil; Karaman, Sait; Karkıner, Canan Sule Unsal; Can, Demet (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2016)
Introduction : Platelets play important roles in airway inflammation and are activated in inflammatory lung diseases, including asthma. Aim :We evaluated the mean platelet volume (MPV), used as a marker of platelet activation, in asthmatic patients during asymptomatic periods and exacerbations compared to healthy controls to determine whether MPV can be used as an indicator of inflammation. Material and methods :Our patient group consisted of95 children with exacerbation of asthma who were admitted to our allergy clinic. The control group consisted of 100 healthy children matched for age, gender, and ethnicity. Mean platelet volume values of the patient group obtained during exacerbation of asthma were compared to those of the same group during the asymptomatic period and with the control group. We investigated factors that can affect the MPV values of asthma patients, including infection, atopy, immunotherapy treatment, and severity of asthma exacerbation. Results :The patient group consisted of 50 (52.6%) boys and 45 (47.4%) girls with a mean age of 125 ±38 months old. Mean MPV values in the exacerbation period, the healthy period, and in the control group were 8.1 ±0.8 fl, 8.1 ±1.06 fl, and 8.2 ±0.9 fl, respectively; there were no significant differences between groups (p > 0.05). The severity of asthma, severity of asthma exacerbation, immunotherapy, coinfection, eosinophil count, and IgE level also had no effect on MPV (p > 0.05). Conclusions : Although platelets play a rolein the pathophysiology of asthma, MPV measurement is insufficient to detect inflammation through platelets